Primary medication non-adherence at Counties Manukau Health Emergency Department (CMH-ED), New Zealand: an observational study - Nataly Dominica Martini; Bert van der Werf; Deborah Bassett-Clarke (BMJ Open)
Objectives To measure primary medication non-adherence (failure to fill prescription medicines) in patients discharged from the emergency department (ED), and to determine whether sociodemographic factors, smoking status and access to a general practitioner affect prescription filling. Little is known about primary medication non-adherence in EDs, and less so in New Zealand (NZ). Identifying reasons for non-adherence will enable development of strategies to improve adherence and reduce morbimortality.Design and setting An observational study based on patient data from the ED of a large public hospital in South Auckland, NZ.Participants Data were collected from 1600 patients discharged between 28 April–6 May and 28 July–9 August 2014. Data were included if patients were residents within the Auckland Regional Public Health Service boundaries, admitted to ED and discharged with a prescription. Data were excluded if patients were admitted to another ward, transferred to another hospital or left the ED without seeing a doctor.Results 992 patients were included in the study, the majority were under 10 years (32.6%), of Pacific Island descent (42.8%), NZ-born (67.7%) and living in the most socioeconomically deprived areas (78.1%). Almost 50% of patients failed to fill all prescription medications. Simple linear regression analysis indicated that non-adherence was significant for those 10–24 years (n=236; adherence=47.2%; p<0.05), of NZ Māori ethnicity (n=175; 51.3%; p=0.01), unemployed (n=77; 46.8%; p<0.01), homemakers (n=66; 45.7%; p<0.01), students (n=228; 55.6%; p<0.05) and cigarette smokers (n=139; 50.3%; p<0.01). Following multivariable analysis, the strongest predictors for non-adherence were those aged between 10 and 17 years (n=116; p<0.01), the unemployed (n=77; p=0.01) and homemakers (n=66; p=0.01).Conclusions Age and occupation were the greater predictors of non-adherence; however, no other significant differences were found. Since this study, changes to prescription co-payments have been made. Further research is warranted to assess whether this change has more recently affected the rates of non-adherence.